2020
DOI: 10.4103/jfmpc.jfmpc_1094_19
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of herbal medicine, acupressure, and acupuncture in the menopausal symptoms: An evidence-based systematic review study

Abstract: Background: Menopause is an important physiological phenomenon in women's lives. Women's concern about taking the hormone treatment to ease menopausal symptoms is increasing. Over the past decade, the use of complementary and alternative medicine for the treatment of menopausal problems instead of hormone therapy has increased. Objective: This study aimed to investigate the role of herbal medicine, acupressure, and acupuncture in the menopausal symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…2). The women's attitudes toward menopause are strongly influenced by social, cultural, and economic settings in which they live and may also reflect the differences in treatment modes for or perceptions of its symptoms 16,21 . Approximately two-thirds of participants had an academic level of college or higher, and 46% (274) were employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The women's attitudes toward menopause are strongly influenced by social, cultural, and economic settings in which they live and may also reflect the differences in treatment modes for or perceptions of its symptoms 16,21 . Approximately two-thirds of participants had an academic level of college or higher, and 46% (274) were employed.…”
Section: Discussionmentioning
confidence: 99%
“…they live and may also reflect the differences in treatment modes for or perceptions of its symptoms. 16,21 Approximately two-thirds of participants had an academic level of college or higher, and 46% (274) were employed. We found that education level was the only significant predictor of knowledge about menopause.…”
Section: Shahzad Et Almentioning
confidence: 99%
“…Accumulating evidence suggests that acupunctureinduced temperature control and reduction in hot flushes among climacteric women is achieved by elevating betaendorphin level and suppressing GnRH secretion. 191 These benefits of acupuncture were validated again in PMD rats and were accompanied by a significant reduction in depressionlike behavior. 124,127,128 Interestingly, serotonin regulates thermoregulation and peripheral vasculature.…”
Section: Dovepressmentioning
confidence: 88%
“…Approximately 51% of women use complementary and alternative medicine (CAM) and more than 60% perceive it to be effective for MSs (Johnson et al, 2019). Moreover, requesting a “natural” approach has become a considerable trend worldwide, so nutraceuticals, with medicinal properties, extracted from food or plants are increasingly used for this purpose (Ebrahimi et al, 2020; Mehrnoush et al, 2021).…”
Section: Introductionmentioning
confidence: 99%